Encyclopedia of Radicals in Chemistry, Biology and Materials 2012
DOI: 10.1002/9781119953678.rad031
|View full text |Cite
|
Sign up to set email alerts
|

Radicals and Carbohydrates

Abstract: CO Me [Ru(bpy) 3 ](BF 4 ) 2 iPr 2 NEt, hn CO 2 Me AcO AcO AcO 21  EtO 2 C CO 2 Et Me N Me 28 H AcO 23 65 Scheme 7 Synthesis of C-ketosides by intermolecular addition of C-glycos-1-yl radicals to double bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 299 publications
(285 reference statements)
0
16
0
Order By: Relevance
“…Radical-mediated transformations have featured prominently in the history of carbohydrate synthesis. Although a detailed discussion of the historical aspects of radical methods in carbohydrate synthesis is outside the scope of this review, past efforts have enabled a wide range of valuable transformations. , Historically, the selective generation of a desired sugar radical required prefunctionalization of the substratefurnishing the sugar with a weak bond susceptible to homolytic or mesolytic scissionand necessitated the application of stoichiometric reagents or harsh conditions. That is, challenges attendant to radical generation prevented the full realization of radical reactions to transform carbohydrate feedstocks.…”
Section: Introductionmentioning
confidence: 99%
“…Radical-mediated transformations have featured prominently in the history of carbohydrate synthesis. Although a detailed discussion of the historical aspects of radical methods in carbohydrate synthesis is outside the scope of this review, past efforts have enabled a wide range of valuable transformations. , Historically, the selective generation of a desired sugar radical required prefunctionalization of the substratefurnishing the sugar with a weak bond susceptible to homolytic or mesolytic scissionand necessitated the application of stoichiometric reagents or harsh conditions. That is, challenges attendant to radical generation prevented the full realization of radical reactions to transform carbohydrate feedstocks.…”
Section: Introductionmentioning
confidence: 99%
“…In previous papers, we have studied that the anomeric alkoxyl radical (i.e., II , Scheme ) β-fragmentation (ARF) of sugars initiated under oxidative or reductive conditions. We have shown that with the system (diacetoxyiodo)­benzene (DIB)/I 2 , the reaction mechanism is strongly dependent on the polarity of the C2 substituent .…”
Section: Introductionmentioning
confidence: 99%
“…For synthetic applications, Bernd Giese's group also made carbohydrate radicals available for the formation of carbon-carbon bonds under mild conditions [10]. Due to steric interactions, carbohydrates provide high stereoselectivities [11,12], and the importance of such reactions has been reviewed many times [13][14][15][16][17][18]. Furthermore, under appropriate conditions, 2-deoxy sugars can be synthesized from bromo sugars in only one step [19].…”
Section: Introductionmentioning
confidence: 99%